Digital artery perforator flap for reconstruction of soft tissue defects of the finger distal to the distal interphalangeal joint - the functional outcomes - Akhter, Tahera; Shahin, M.; Muniruzzaman, A. K. M.; Happy, Nurun Nahar; Islam, M. Obaidul; Asif, M. Mosaddeque Hasan (International Surgery Journal, 2025)
Background: Fingertip injuries involving the distal phalanx often lead to functional and aesthetic impairment, requiring reliable reconstruction methods that preserve length, sensation, and mobility while minimizing donor site morbidity. The purpose of the study is to evaluate the functional outcomes of digital artery perforator flap reconstruction for soft tissue defects distal to the distal interphalangeal joint. The aim of the study was to evaluate the functional outcomes of digital artery perforator flap reconstruction for soft tissue defects distal to the distal interphalangeal joint Methods: This prospective observational study at the Department of Plastic Surgery, Dhaka Medical College Hospital, Dhaka, Bangladesh (July 2018 to June 2019) included 20 patients with distal phalanx soft tissue defects. Flaps were raised on distal digital artery perforators, rotated 90°–180°, and donor sites closed primarily or grafted. Postoperative care included dressings, splinting, and early motion. Outcomes were assessed by goniometer; data were analyzed with SPSS v23.0. Results: Among 20 patients, most were males (18, 90%) aged 16–25 years (9, 45%). Machinery injury was most common (9, 45%). Flap length 2.0–4.0 cm, width 1.0–2.0 cm. Wounds were mainly left-sided (11, 55%). Complications included venous congestion (11, 55%) and marginal necrosis (4, 20%), with donor sites mostly uneventful (18, 90%). Full DIP movement achieved in 11 (55%); flap outcome excellent in 14 (70%). Conclusions: DAP flap provides reliable fingertip reconstruction with excellent functional outcomes without compromising the digital artery.